China's compliance with the Montreal Protocol - Zhao, J; Ortolano, L (International Network for Environmental Compliance and Enforcement, 1998)
An analysis of the household refrigeration sector and the foams sector investigates how Chinese enterprises have complied with the Montreal Protocol on Substances That Deplete the Ozone Layer. We demonstrate that the performance of the household refrigeration sector in reducing ozone-depleting substance consumption is superior to the performance of the foams sector, and we present two explanations for this outcome. First, market demand matters. The influence of the global market, multinational corporations, intense (and occasionally misleading) advertising about non-CFC products, and severe competition for consumers caused China’s principal refrigerator manufacturers to adopt nonCFC production technologies. Similar incentives did not exist for enterprises in the foams sector. Second, industrial structure matters. The foams sector includes a large number of small enterprises with limited financial and technical capability and weak access to information and technology, and these factors obstructed technological change. In general, assistance from the multilateral fund established under the Montreal Protocol has motivated enterprises to shift to ozone-depleting substance reduction technologies, but complex and lengthy procedures for accessing the multilateral fund, difficulties in finding appropriate suppliers of non-CFC technologies and insufficient financial and technical capabilities of many enterprises have slowed down this shift. Our results provide a foundation for better compliance in the future.